Career Preference in Teenagers: Social and Psychological Factors - Sh., Jumaev A. (International Journal on Integrated Education, 2023)
The pedagogy and psychology of emotional relations regarding human creativity, love, and friendship feelings, as well as the social activity of the individual as a factor in guiding young people to the profession, are examined in this article. The analysis is based on the scholars and thinkers of the East.